PENGETAHUAN DAN PENGGUNAAN TUMBUHAN KOWALA (AREN) PADA MASYARAKAT MUNA DI KECAMATAN WATOPUTE KABUPATEN MUNA - Basri, La Ode Ali (Jurnal Penelitian Budaya, 2020)
The purpose of this study is to know and analyze the traditional Muna knowledge in Watopute District regarding the perception, management, and utilization of kowala (sugar palm/) plants. Data collection is carried out through in-depth interviews, engaged observations, and focused discussions. Data analysis is performed through data reduction, data presentation, and drawing conclusions. The results showed that the community perceive sugar palm plants as special plants because all parts of the plant, from the roots to the tops, are useful for humans and are useful in creating ecological balance. The Watopute community makes the sugar palm plant as a teacher of life institutionalized in a value system through the traditional expression "dodadi beano peda kowala, nobhari ghuluhano mbali alamu" (humans must live like sugar palm, which brings many benefits to the universe). The using of sugar palm trees in the Watopute community is carried out in a traditional manner in accordance with the local wisdom of the local community obtained from their ancestors from generation to generation. The most used part of the sugar palm plant by the community is the male of sugar palm flower which is processed to produce kameko (sap). The male sugar palm flowers are most used because this part is easy to do and has good marketing potential, so it is more profitable economically.